2011
DOI: 10.1063/1.3623760
|View full text |Cite
|
Sign up to set email alerts
|

Response of graphene to femtosecond high-intensity laser irradiation

Abstract: We study the response of graphene to high-intensity 10^11-10^12 Wcm^-2, 50-femtosecond laser pulse excitation. We establish that graphene has a fairly high (~3\times10^12Wcm^-2) single-shot damage threshold. Above this threshold, a single laser pulse cleanly ablates graphene, leaving microscopically defined edges. Below this threshold, we observe laser-induced defect formation that leads to degradation of the lattice over multiple exposures. We identify the lattice modification processes through in-situ Raman … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
125
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 19 publications
9
125
2
3
Order By: Relevance
“…Currie et al studied the femtosecond laser induced damages on graphene and has shown that even at a very low laser fluence of 14 mJ/cm 2 , some modifications of graphene lattice can be observed [11]. Roberts et al studied 50 fs laser pulse interaction with graphene and has demonstrated a clean micro-hole formed on graphene by a single pulse laser shot [12]. Several other techniques including femtosecond laser direct-writing of 40 nm thick graphene films [13] and graphene oxides films [14,15] have been proposed.…”
mentioning
confidence: 99%
“…Currie et al studied the femtosecond laser induced damages on graphene and has shown that even at a very low laser fluence of 14 mJ/cm 2 , some modifications of graphene lattice can be observed [11]. Roberts et al studied 50 fs laser pulse interaction with graphene and has demonstrated a clean micro-hole formed on graphene by a single pulse laser shot [12]. Several other techniques including femtosecond laser direct-writing of 40 nm thick graphene films [13] and graphene oxides films [14,15] have been proposed.…”
mentioning
confidence: 99%
“…The increase in the potential energy was 27.90 eV after the pulse had decayed, which corresponds to an effective fluence of 8.20 mJ/cm 2 . The effective fluence depends on the periodic boundary conditions, 20 33 Recently a threshold of 14 mJ/cm 2 for a damage has been reported. 34 These results indicate the stability of the underlying graphene sheet.…”
mentioning
confidence: 99%
“…We note that below the damage threshold intensity, no saturation of the graphene absorption has been observed. This is in contrast to experiments with short (ps) laser pulses, where the damage threshold [26] is several orders of magnitude larger than the saturation intensity [27].…”
mentioning
confidence: 39%